Troska o stałą formację intelektualną młodych prezbiterów w kontekście nowej ewangelizacji - Celary, Ireneusz (Studia Pastoralne, 2026)
Evangelization is a challenge for the whole Church. In this work priests participate in a special way. Bishops and presbyters by the sacrament of Holy Orders are capable and obliged to preach crucifixion and resurrection of Jesus Christ. He possesses words of life which are answers to our existential questions. Young presbyters taking responsibility for church communities have to continue their formation through permanent formation. It should deepen theological and philosophical knowledge. Thanks to that young priests are able to transfer God teaching to contemporary men.